2003
DOI: 10.2355/isijinternational.43.1461
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Steelmaking Slag Addition on Growth of Marine Phytoplankton

Abstract: Culture experiments of a natural phytoplankton assemblage collected from coastal surface water and a mono-specifically cultured diatom were conducted to investigate the possibility of steelmaking slags to use as a nutrient resource for marine phytoplankton. Two kinds of slags, a decarburization slag and a dephosphorous slag, were tested in batch cultures under freely drifting pH. Leaching experiment to determine dissolution of nutrient elements from the slags demonstrated that phosphate and reactive silicate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 20 publications
(21 reference statements)
1
15
0
Order By: Relevance
“…Protein content increases should also be associated with iron dissolution. This idea is also supported by the increase in marine phytoplankton fluorescence intensity by iron from SMS (SMS diameter: 5-20 μm) [23]. Another explanation for the change in protein content is the pH increase.…”
Section: Dna Profile Of S Platensis M135mentioning
confidence: 49%
“…Protein content increases should also be associated with iron dissolution. This idea is also supported by the increase in marine phytoplankton fluorescence intensity by iron from SMS (SMS diameter: 5-20 μm) [23]. Another explanation for the change in protein content is the pH increase.…”
Section: Dna Profile Of S Platensis M135mentioning
confidence: 49%
“…Haraguchi et al 29) also reported a similar pH increase with the addition of 33 mg L Ϫ1 of but with no growth inhibition. Therefore, the present condition did not negatively affect the growth of phytoplankton.…”
Section: Resultsmentioning
confidence: 65%
“…The fine grains also allow the elements to easily dissolve in culture media as reported previously. 25,26,28,29) …”
Section: Steelmaking Slagmentioning
confidence: 99%
See 1 more Smart Citation
“…10) Steel slag also can create reef-like habitat for fishes 11) and promote growth of some marine phytoplankton. 12) On the other hand, a large amount of calcium in the form of uncombined calcium called 'free lime' 13,14) can be dissolved into seawater or sediment from slag. However, with the application of slag to the marine environment, the free lime is easily transformed to calcium hydroxide through hydration reactions.…”
Section: Introductionmentioning
confidence: 99%